Developing the Content Validity Index of a SERVQUAL Instruments in the Public Sector of Nepal - Palikhe, Amin (Prithvi Journal of Research and Innovation, 2025)
The content validity index is one of the methods of the instrument development, well designed and relevant tool of scale development. There are rarely used scale development instruments in the Nepali public sector and particularly used to gather the reliable data in the medical and health field. This is the foremost calculation of value of the content validation of questionnaire items to assess the perceived service quality delivery instrument in the perspective of Nepali public sector, which uses the modified Delphi method for the development of scale instrument. Therefore, this study aims to explore and to validate the questionnaire items to assess the perceived service quality by using the content validation index (CVI) method. The value of content validation of developed questionnaire items has more than 0.70 cut-off point. Among the 87 questionnaire items, 33 items got a sufficient agreement from the experts, which is sufficiently validates in terms of a number of experts in the panel, in which there were eleven experts with an individual difference. The 24 items are more than 60% of agreement, as the refinement list and rest of the items (less than 0.60) are eliminated. In conclusion, it is more transparent, accurate, consistent and reliable of assessment questionnaire items based on the evidence from the calculation of content validation index. Therefore, the calculation of CVI is a theoretically and methodologically proven method, practically to apply for scale development and significantly aids researchers and practitioners. It is recommended and that further suggestions to confirm the assessment questionnaire items are made by using the advance statistical tools like the exploratory factor analysis and confirmatory factor analysis and in order to undergo a pilot study.